"I am willing to do both well": Chinese academic mothers facing tension in family and career. - Bao, Li; Wang, Guanghua (Frontiers in psychology, 2022)
Academic mothers perform intersected roles. They carry out their profession in workplaces, while they take the "second shift" of motherhood back to their families. The contested expectations in family and career built by the heterosexual matrix cause tension to academic mothers. We qualitatively investigate the interview data of six Chinese women academics on how they perform to negotiate their motherhood and academic work in the context of Chinese higher education, driven by the Butlerian theoretical concept of the heterosexual matrix. The findings suggest that Chinese academic mothers play a zero-sum game between being mothers and being academics, deriving from their ontological responsibilities of motherhood. We conclude that in the masculine academia, these women academics help maintain the heterosexual matrix by satisfying the gender normativity when they negotiate their performances in their family and career; meanwhile, most have developed some strategies to achieve their career advancement.; Competing Interests: The authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest. (Copyright © 2022 Bao and Wang.)
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; chine; conciliation famille-travail; famille; femmes* universitaires; hétérosexisme; maternité; matrice hétérosexuelle; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail

“I have no room of my own”: COVID-19 pandemic and work-from-home through a gender lens - Chauhan, Priyanshi (Gender Issues, 2022)
Working from home is not gender neutral. As the COVID-19 pandemic has relocated all non-essential work to the home setting, it becomes imperative to examine the phenomenon through a gender lens. Accordingly, I conducted a qualitative study using semi-structured interviews with 30 dual-earning married couples in India to study the gendered work-from-home experiences of men and women during the pandemic. The findings suggest that the pandemic has disproportionately increased the burden of unpaid work for women as compared to men. Women are negotiating gendered time–space arrangements within their households with the allocation of limited resources being in favor of men. When this interacts with work, gender inequalities are reinforced both at work and home. Gender roles and unpaid work determine women’s choices regarding when and where to work, boundary management between work and non-work domains, and their experiences of social isolation. Further, gender roles have also affected women’s decisions regarding returning to work post-pandemic, where some women may not be returning to work at all. Finally, the paper identifies how gender intersects with the existing conceptual frameworks of working from home, and makes a strong case for integrating gender considerations in the work-from-home policies. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; conciliation famille-travail; covid-19; famille; hétérosexisme; inde; inégalités; inégalités hommes-femmes; pandémie; projet charge mentale; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; travail; travail gratuit

Gender inequities in household labor predict lower sexual desire in women partnered with men - Harris, Emily A; Gormezano, Aki M.; van Anders, Sari M. (Archives of Sexual Behavior, 2022)
Low sexual desire in women is usually studied as a problem, one that is located within women. However, other possibilities exist, including known gender inequities related to heteronormative gender roles. In this study, we provide the first test of the theory that heteronormativity is related to low sexual desire in women partnered with men, focusing specifically on inequities in the division of household labor. In two studies with women who were partnered with men and had children (Study 1, N = 677; Study 2, N = 396), performing a large proportion of household labor was associated with significantly lower sexual desire for a partner. Together, the results suggest that this association was mediated by both perceiving the partner as a dependent and perceiving the division of labor as unfair. These results support the heteronormativity theory of low sexual desire in women partnered with men, and show that gender inequities are important, though understudied, contributors to low desire in women partnered with men. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; désir; hétéronormativité; hétérosexisme; projet charge mentale; périodes historiques; santé; sexualité; systèmes d'oppressions; thématiques; travail; travail domestique

Comment la crise fait-elle ressortir les inégalités de genre ? - Plumauzille, Clyde (2020)
Aides-soignantes, caissières, aides à domicile… ce sont majoritairement des femmes qui se retrouvent en première ligne contre le virus. Comme le rappelle l’historienne Clyde Plumauzille dans ce podcast, ces inégalités ne sont pas nouvelles, la prise en charge d’autrui au sein du foyer ou dans la société étant historiquement dévolue aux femmes.
Performers: _:n2788
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; care; charge mentale; confinement; covid-19; histoire et politique; hétérosexisme; inégalités; projet charge mentale; périodes historiques; rapports sociaux de sexe; ressource en ligne; santé; sexisme; systèmes d'oppressions; thématiques; travail; travail domestique; violences; violences conjugales

Travailler la terre et déconstruire l’hétérosexisme: expérimentations écoféministes - Rimlinger, Constance (Travail, genre et sociétés, 2019)
À partir de l’ethnographie de trois lieux ruraux (deux fermes et un gîte) tenus par des femmes lesbiennes et/ou queer qui s’inscrivent dans une critique écologiste et anticapitaliste de la société tout en questionnant les normes de genre et de sexualité, nous interrogerons la signification de ces choix de vie alternatifs au regard de l’identité des actrices et de la manière dont ils enrichissent la compréhension de la constellation des mouvements écoféministes. Nous observerons qu’avec le déplacement de la ville vers la campagne, et du monde salarié vers l’agriculture de subsistance, elles doivent mettre en place de nouvelles stratégies pour lutter contre l’isolement et s’intégrer localement. Simultanément, ce retour à la terre leur offre de nouvelles possibilités d’émancipation, d’engagement et de soutien aux femmes et aux minorités. Le travail agricole, l’engagement féministe et la politisation du quotidien constituent les différentes facettes d’un même projet : celui de chercher une voie plus juste et plus durable pour notre société.
Keywords: 2000 à aujourd'hui; 2010-2019; agriculture; approches et analyses; care; com5170; cours; discipline; environnement; europe; france; hétérosexisme; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; séparatisme lesbien; thématiques; travail; vie rurale; écoféminisme; écologie queer

King King théorie - Despentes, Virginie (Grasset, 2006)
J'écris de chez les moches, pour les moches, les frigides, les mal baisées, les imbaisables, toutes les exclues du grand marché à la bonne meuf, aussi bien que pour les hommes qui n'ont pas envie d'être protecteurs, ceux qui voudraient l'être mais ne savent pas s'y prendre, ceux qui ne sont pas ambitieux, ni compétitifs, ni bien membrés. Parce que l'idéal de la femme blanche séduisante qu'on nous brandit tout le temps sous le nez, je crois bien qu'il n'existe pas. V.D.
Keywords: 2000 à aujourd'hui; 2000-2009; anticapitalisme; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; europe; fem1000; fem7000; france; hétérosexisme; identités LGBTQIA2+; lit3220; littérature; premier cycle; périodes historiques; régions géographiques; sexualité; systèmes d'oppressions; thématiques; travail; travail du sexe; violences; violences sexistes et sexuelles; études littéraires